Explore the Value of Dual Source Computer Tomography Automatic Tube Current Regulation in Reducing the Radiation Dose of CTA in Lower Extremity Vessels - Xin Hu (Frontiers in Surgery, 2022)
ObjectiveTo investigate the value of dual source computer tomography automatic tube current regulation in reducing the radiation dose of CTA in lower limb vessels.MethodsFrom February 2020 to December 2021, 64 patients with lower limb artery CTA were selected in our hospital because of the symptoms of foot ischemia. According to the random number table, patients were divided into control group (treated with fixed tube current technology) and observation group (treated with automatic tube current regulation technology), with 32 cases in each group. All patients underwent a dual source computer tomography scan. Control group: tube voltage 120 kV, tube current 250 mA; Observation group: tube voltage was 80 kV, and reference tube current was 80–380 mA. Other scanning conditions of patients in the two groups were the same. CTDIvol, DLP and calculated SNR and CNR were recorded to obtain the ED.ResultsThe values of CTDIvol, DLP and ED in the observation group were lower than those in the control group (P < 0.05). There was no significant difference in CT value, SD value, SNR value and CNR value of the femoral artery segment, popliteal artery segment and posterior tibial artery segment between the two groups (P > 0.05). The image quality scores of patients in the control group were slightly higher than those in the observation group, but there was no statistical difference between the two groups (P > 0.05).ConclusionThe application of dual source computer tomography automatic tube current adjustment technology in CTA examination of lower limb vessels can automatically adjust the compensation output and realize the output of different tube currents in different thicknesses, densities and angles. On the premise of not affecting the image quality, the radiation dose in the scanning process to the maximum extent, and reasonably protect the examined patients.